Given f(x) = x+2 and g(x) = x-4 solve for (fg)(x)

Question

Given f(x) = x+2 and g(x) = x-4 solve for (fg)(x)

in progress 0
Josie 3 weeks 2021-09-09T08:44:23+00:00 2 Answers 0

Answers ( )

    0
    2021-09-09T08:45:27+00:00

    Answer:  f(g(x)) = x – 2

    Step-by-step explanation:

    f(x) = x + 2            

    g(x) = x – 4

    f(g(x)) = f(x – 4) = (x – 4) + 2        replaced x with x – 4

                           = x – 2                 simplified

    0
    2021-09-09T08:46:11+00:00

    Answer: the answer is x^2-2x-8

    Step-by-step explanation:

    You use the foil method. Edg 2029

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )